A Chromosomal Inversion of 46XX, inv (6) (p21.3p23) Connects to Congenital Heart Defects - Cheng, Liangping; Tang, Yanlai; Lin, Yuese; Ba, Hongjun; Ding, Yiqian; Chen, Dubo; Liu, Min; Pan, Peizhen; Qin, Youzhen; Huang, Zhan-Peng (Frontiers in Cardiovascular Medicine, 2020)
Congenital heart defects (CHDs) represent the most common human birth defects. Ventricular septal defect (VSD) is the most common subtype of CHDs. It has been shown that about 20–40% of VSDs are close related to chromosomal aneuploidies or Mendelian diseases. In this study, we report a pedigree with VSD associated with a balanced paracentric inversion of chromosome 6, inv (6)(p21.3p23), a rarely reported CHD-associated chromosomal abnormality related to the fragile site at 6p23. We have found major clinical features of the proband include CHDs (ventricular septal defect, severe pulmonary hypertension, tricuspid regurgitation and patent foramen ovale), severe pneumonia and presented with growth retardation. Our study reports a rare chromosomal abnormality connected to CHDs, which may represent a new genetic etiology for VSD.